THE CORRELATION OF TOTAL FLAVONOID AND TOTAL PHENOLIC WITH ANTIOXIDANT ACTIVITY OF SINGLE BULB GARLIC (Allium Sativum) FROM TAWANGMANGU AND MAGETAN - Ika Buana Januarti; Hudan Taufiq; Sulistyaningsih Sulistyaningsih (Sanata Dharma University, 2019)
Flavonoids and phenolics are compounds with hydroxyl groups (-OH) bound to aromatic rings which enable them to react with reactive oxygen species and eliminate free radical activity. Single bulb garlic (Allium sativum var. solo garlic) is known to have antioxidant activity which comes from the phenolic groups. This study aims to determine the correlation of total flavonoid and phenolic levels with the antioxidant activity of ethanolic extracts from single bulb garlic grown in Magetan and Tawangmangu regions. This study included an observational analytic study with a cross-sectional design. Total flavonoid levels were measured by colorimetric method and total phenolic levels were measured by Folin-ciocalteu method using Spectrophotometric UV-Vis. Antioxidant activity was measured by DPPH method at a wavelength of 517 nm. The data analysis used was multiple linear regression. The results showed that the extract of single bulb garlic from Magetan had total flavonoids of 12,1833 0,1943 mg QE/gram, total phenolics of 70,244 mg GAE/gram, and antioxidant activity with an IC50 value of 20,216 ppm. The extract of single bulb garlic from Tawangmangu contained total flavonoids of 14,4833 0,5911 mg QE/gram, total phenolics of 92,222 mg GAE/gram, and antioxidant activity with an IC50 value of 13,777 ppm. The conclusion of this study is that there is a significant correlation of total flavonoid and total phenolic content with antioxidant activity.